Peran Motivasi Intrinsik, Lingkungan Kerja Fisik dan Kepuasan Kerja Terhadap Komitmen Afektif PT. XYZ - Audi Aviari; Syahrian (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
his study aims to determine the role of intrinsic motivation, physical work environment, and job satisfaction on affective commitment. This research was conducted at PT. XYZ, by taking 67 employees as research samples using purposive sampling technique. Collecting data using observation and questionnaire methods. The data analysis technique used is multiple regression analysis. Based on the research conducted, the results of the analysis show that job satisfaction influences affective commitment. Meanwhile, intrinsic motivation and physical work environment have no effect on affective commitment.